2003
DOI: 10.1097/01.ta.0000046256.80836.aa
|View full text |Cite
|
Sign up to set email alerts
|

Current Diagnostic Approaches Lack Sensitivity in the Diagnosis of Perforated Blunt Small Bowel Injury: Analysis from 275,557 Trauma Admissions from the EAST Multi-Institutional HVI Trial

Abstract: Alone or in combination, current diagnostic approaches lack sensitivity in the diagnosis of perforated SBI. Improvements in diagnostic methods and approaches are needed to ensure the prompt diagnosis of this uncommon but potentially devastating injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
211
3
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(234 citation statements)
references
References 23 publications
7
211
3
13
Order By: Relevance
“…However, if free fluid is present without concomitant CT scan evidence of solid organ injury, its etiology should be evaluated and other CT signs of GI perforation should be searched for [7]. Free fluid without solid organ injury was found by Fakhry and coworkers to be associated with an 84.2% incidence of small bowel injury [17]. The combination of free fluid and pneumoperitoneum increased the sensitivity in detecting perforated small bowel injury to 97% [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, if free fluid is present without concomitant CT scan evidence of solid organ injury, its etiology should be evaluated and other CT signs of GI perforation should be searched for [7]. Free fluid without solid organ injury was found by Fakhry and coworkers to be associated with an 84.2% incidence of small bowel injury [17]. The combination of free fluid and pneumoperitoneum increased the sensitivity in detecting perforated small bowel injury to 97% [9].…”
Section: Discussionmentioning
confidence: 99%
“…Bhatti et al found stab injury as the commonest mode of injury affecting mostly large intestine (40%) 4 . Fakhry SM et al showed that most of abdominal injuries affect the jejunum (64%) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have pointed out, that bruising in a seat belt pattern was associated with intra-abdominal injury in 20-60% of cases [6]. The risk of perforated bowel injury increased by a 2.4 factor whenever seat belt bruising was detected [7]. In contrast, isolated findings of bruising without associated abdominal pain or guarding, was associated with low risk of intra-abdominal injury [8].…”
Section: Case Presentationmentioning
confidence: 92%